Characterization of the complete mitochondrial genome of Uvitellina sp., representative of the family Cyclocoelidae and phylogenetic implications - Suleman; Khan, Mian Sayed; Heneberg, Petr; Zhou, Cheng-Yan; Muhammad, Nehaz; Zhu, Xing-Quan; Ma, Jun (Parasitology research, 2019)
Mitochondrial (mt) DNA has been useful in revealing the phylogenetic relationship of eukaryotic organisms including flatworms. Therefore, the use of mitogenomic data for the comparative and phylogenetic purposes is needed for those families of digenetic trematodes for which the mitogenomic data are still missing. Molecular data with sufficiently rich informative characters that can better resolve species identification, discrimination, and membership in different genera is also required for members of some morphologically difficult families of trematodes bearing few autapomorphic characters among its members. Here, the internal transcribed spacer (ITS) region of nuclear ribosomal DNA (rDNA) and the complete mt genome of the trematode Uvitellina sp. (Cyclocoelidae: Haematotrephinae) was determined and annotated. The mt genome of this avian trematode is 14,217 bp in length, containing 36 genes plus a single non-coding region. The ITS rDNA sequences were used for the pairwise sequence comparison of Uvitellina sp. with European cyclocoelid species, and the mitochondrial 12 protein-coding genes (PCGs) and two ribosomal RNA genes were used to evaluate the position of the family within selected trematodes. The ITS rDNA analysis of Uvitellina sp. showed less nucleotide differences with Hyptiasmus oculeus (16.77%) than with other European cyclocoelids (18.63-23.58%). The Bayesian inference (BI) analysis using the 12 mt PCGs and two rRNA genes supported the placement of the family Cyclocoelidae within the superfamily Echinostomatoidea (Plagiorchiida: Echinostmata). The availability of the mt genome sequences of Uvitellina sp. provides a novel resource of molecular markers for phylogenetic studies of Cyclocoelidae and other trematodes.
Keywords: DNA, Ribosomal Spacer; Sequence Analysis, DNA; mitochondrie; Nuclear ribosomal DNA; Bayes Theorem; Phylogenetic implications; DNA, Mitochondrial; Birds; DNA, Ribosomal; genom mitochondriální; Bayesova věta; Echinostomatidae; Cyclocoelidae; Base Sequence; sekvence nukleotidů; zvířata; mitochondriální DNA; fylogeneze; ribozomální DNA; sekvenční analýza DNA; Mitochondria; Mitochondrial genome; Uvitellina sp.; ptáci; Genome, Mitochondrial; Phylogeny; mezerníky ribozomální DNA; Animals